EEGmagic: programa para analizar señales electroencefalog´ráficas - Guevara Pérez, Miguel Ángel; Hernández González, Marisela (Revista Mexicana de Ingenieria Biomedica, 2009)
The quantitative analysis of electroencephalographic activity (EEG) consitutes a useful tool that makes it possible to relate changes in cerebral electrical activity to cognitive and behavioral functions under a variety of experimental conditions. Their recording and analysis are currently carried out primarily through the use of computer programs. This study presents a computarized program (EEGmagic) that was elaborated for the Windows operating system using the Delphi language, and that is designed to analyze EEG signals and facilitate their quantitative exploration. To do so, the program applies Rapid Fourirer Transform to the EEG signals of one or more groups of subjects in order to obtain both absolute and relative potentials spectra. It also calculates the correlation spectra, both interhemispheric and intrahemispheric, and, finally, applies parametric statistical analyses to these potential and correlation spectra. Statistical analyses are applied to each individual frequency and to frequencies grouped in bands. Unlike other programs, EEGmagic is simple and inexpensive. It obtains the results files with the corresponding statistical significances rapidly and with precision; thus, EEGmagic may constitute an important tool for the study of cerebral functionality and behavior.